The Relationship Between Short-Term Surrogate Endpoint Indicators and mPFS and mOS in Clinical Trials of Malignant Tumors: A Case Study of Approved Molecular Targeted Drugs for Non-Small-Cell Lung Cancer in China - Rui, Mingjun; Wang, Zijing; Fei, Zhengyang; Wu, Yao; Wang, Yingcheng; Sun, Lei; Shang, Ye; Li, Hongchao (Frontiers in Pharmacology, 2022)
Objective Due to the initiation of the priority review program in China, many antitumor drugs have been approved for marketing after only phase I and phase II clinical trials and the use of short-term surrogate endpoint indicators. This study used approved targeted drugs for the treatment of non-small-cell lung cancer (NSCLC) in China as an example to evaluate the association between short-term surrogate endpoints (objective response rate (ORR) and disease control rate (DCR)) and median progression-free survival (mPFS) and median overall survival (mOS). Methods 5 databases, i.e., MEDLINE, Embase, Cochrane Library, China National Knowledge Infrastructure (CNKI), and Wanfang Data were searched, for phase II or phase III clinical trials of all molecular targeted drugs that have been marketed in China for the treatment of NSCLC. After screening the literature and extracting information, univariate linear regression was performed on the short-term surrogate indicators and mPFS and mOS to explore the relationship. Results A total of 63 studies were included (25 studies with only ORR, DCR, and mPFS and 39 studies with ORR, DCR, mPFS, and mOS). In terms of the targeted drugs for the treatment of NSCLC, in addition to the good linear relationship between DCR and mOS, all other surrogate endpoint indicators had excellent linear relationships with mPFS and mOS. In addition, there was also an excellent linear relationship between mPFS and mOS. Conclusions For targeted drugs for the treatment of NSCLC, short-term surrogate endpoint indicators such as ORR and DCR may be reliable surrogate indicators for mPFS and mOS. However, whether short-term surrogate endpoint indicators can be used to predict final endpoints remains to be verified.